AQUEOUS EMULSION MIXTURE PREPARATION DEVICE - Ergashev Bahodir Husanovich (Journals Park Publishing, 2023)
In the article, issues related to the justification of the technical characteristics and parameters and structural structure of the device for preparing the aqueous emulsion mixture are studied.
Keywords: Emulsion, bearing, housing, pulley, plate, cylindrical vessel, belt.